The Outcome after Surgery of Patients with Congenital Cataract in the Outpatient Clinic of RSUD Dr. Soetomo Surabaya in January 2014 – January 2017 - Nuramalia, Lady Sherly; Wahyuni, Indri; Gunawan, Prastiya Indra (Universitas Airlangga, 2019)
Introduction: Congenital cataract is a leading cause of childhood blindness. Congenital cataract is characterized by an opacification of the lens that has existed from birth or shortly after birth. Congenital cataract can occur unilateral or bilateral. The cause of congenital cataract can be idiopathic, hereditary, chromosomal disorders, metabolic disorders, and infections. The use of intraocular lens implantation can provide better visual results. Whereas the results of cataract surgery with aphakia glasses correction showed poor results. This study aims to find out the outcome after surgery of congenital cataract patients in the outpatient clinic of RSUD DR. Soetomo Surabaya.Methods: This research was a descriptive retrospective study. Samples were patients with congenital cataract diagnosis in the Outpatient Clinic of RSUD Dr. Soetomo Surabaya in January 2014 – January 2017.Results: The results showed that there were 21 patients with congenital cataract. The most outcome after surgery of the patients with congenital cataract OS and OD were IOL positive, there were 14 (70%) for OS and 14 (77.77%) for OD.Conclusion: Most patient outcomes after surgery was IOL positive.